The Implementation of Inclusive Education at SDN 30 Palembang : Challenges and Supports - Agus Wahyudi; Maria Qibtia; Arief Pamuji (JISPENDIORA Jurnal Ilmu Sosial Pendidikan Dan Humaniora, 2025)
This study aims to describe the implementation of inclusive education at State Elementary School (SDN) 30 Palembang, focusing on the challenges and forms of support faced in its implementation. Inclusive education is an approach that ensures all children, including children with special needs (ABK), get equal access to education in a friendly and open environment. The research method used is descriptive qualitative, the results of the study indicate that the main challenges in the implementation of inclusive education at SDN 30 Palembang were the lack of disability-friendly facilities, as well as the ongoing stigma from the community towards ABK students. Other technical obstacles are the limited ratio of ABK per class set by government policy and the lack of supporting resources. However, this study also found significant support, such as teacher training, principal involvement, and cooperation with external institutions that encourage the sustainability of inclusive education. This study concludes that the implementation of inclusive education at SDN 30 Palembang shows positive developments even though it still faces structural and social challenges. Policy strengthening, teacher capacity building, and community support are needed so that the inclusive education system can run more optimally and sustainably.